Gut-friendly chickpea (Cicer arietinum): Germination as a sustainable approach to reduce flatogenic sugars: IMPACT OF GERMINATION ON α-GALACTOSIDASE ACTIVITY AND FLATOGENIC SUGARS IN CHICKPEA (Indian Journal of Traditional Knowledge (IJTK), 2025)
Chickpea (Cicer arietinum), a widely consumed legume, is rich in proteins and dietary fiber but contains raffinose family oligosaccharides (RFOs), which cause gastrointestinal discomfort due to the absence of alpha galactosidase enzyme in humans. Traditional processing methods, such as germination, have been used to enhance the nutritional and functional properties of legumes. This study investigates the effect of germination on α-galactosidase activity and RFO reduction in two chickpea varieties-Desi (NBeG-49) and Kabuli (NBeG-119). Chickpeas were soaked, germinated for up to 72 h, and analyzed for moisture content, texture, enzyme activity, and RFO levels. The results showed that α-galactosidase activity peaked at 48 h, leading to a significant reduction in RFOs (100% after 72 h in Desi and 60 h in Kabuli). Germination also influenced texture by increasing seed hardness due to structural modifications. SEM analysis revealed increased porosity, facilitating enzymatic action. These findings reinforce germination as a cost-effective, traditional method to improve chickpea digestibility, reducing antinutritional factors while preserving its nutritional value. This approach aligns with indigenous knowledge practices and offers potential applications in functional food development.